Binding Sale and Purchase Agreement and Power of Attorney Over Land in the Perspective of the Principle of Horizontal Separation - Napitupulu, Diana R. W. (Jurnal Smart Hukum (JSH), 2025)
This study explores the application of the horizontal separation principle in land ownership and transfer in Indonesia, focusing on the Binding Sale and Purchase Agreement (PPJB) and the power of attorney in land transactions. The horizontal separation principle, derived from customary law, ensures that land ownership does not automatically include ownership of buildings or plants on the land. This research examines how this principle affects legal processes related to land rights transfers and the challenges it poses in the context of sale and purchase agreements. By analyzing legal documents, court rulings, and relevant literature, the study identifies key issues such as ambiguous ownership rights and procedural complications that arise from the separation principle. The findings highlight the need for legal clarity and reform to enhance property rights protection and dispute resolution effectiveness in Indonesia's land law system.